An evaluation of a coagulation system (Xprecia Stride) for utilisation in anticoagulation management. Issue 1 (13th June 2017) - McCahon, Deborah; Roalfe, Andrea; Fitzmaurice, David A
Abstract : Aim: To evaluate the reliability and performance of the Xprecia Stride coagulometer under the conditions in which it is most likely to be used. Methods: The performance of the Xprecia Stride coagulometer was compared with a local laboratory and the CoaguChek systems routinely used for international normalised ratio (INR) estimation within one primary and one secondary care based anticoagulation clinic in Birmingham. Anticoagulation clinic personnel were trained to use the Xprecia Stride. Patients attending the clinics were eligible if aged ≥18 years and had received warfarin for at least 3 months. Consenting participants provided capillary blood samples for parallel testing on the Xprecia Stride and CoaguChek systems. At the secondary care clinic, a venous blood sample was also collected for laboratory INR estimation. INR results were compared using linear regression analysis and Bland–Altman plots. Results: A total of 102 laboratory and 205 parallel coagulometer INR tests were performed. Linear regression revealed strong correlation between the Xprecia Stride and the laboratory (r=0.83) and between the Xprecia Stride and CoaguChek systems (r=0.92). Within the therapeutic range, agreement between the systems was very good with 87% of the Xprecia Stride and laboratory INR results and 93% of the Xprecia Stride and CoaguChek INR results being within 0.5 INR units of each other. Conclusion: INRs tested using the Xprecia Stride system showed good agreement with the laboratory and CoaguChek systems. Findings indicate that in the hands of the intended users the Xprecia Stride is accurate, reliable and acceptable for use in a routine clinical setting.